2021
DOI: 10.3390/agriculture11040375
|View full text |Cite
|
Sign up to set email alerts
|

Hazard of Contamination with Heavy Metals in Thymus serpyllum L. Herbs from Rural Areas

Abstract: The aim of the research has been to assay the contents of Zn, Cu, Mn, Fe, and Pb in soil and in the organs of wild Thymus serpyllum L. acquired from three natural habitats from the Kuyavia-Pomerania Province (Poland) not exposed to contamination with metals. As compared with the contents of the geochemical background of the soils in the region and the value of enrichment factor (EF), there was noted a considerable content of Pb in the soil from two locations. The Pb content in plant tissues in one of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
6
1
Order By: Relevance
“…In this study, the levels of Cu, Mn, and Zn are higher than the reported WHO maximum permissible limits established for medicinal plants, just as previous studies have reported such high levels of essential metals in medicinal plants [71,72]. The population's health risk within the study was assessed based on the United States Environmental Protection Agency (USEPA) model, where a noncarcinogenic risk assessment of ingesting medicinal plants for children and adults in the study was established based on HQ and HI values.…”
Section: Discussioncontrasting
confidence: 45%
“…In this study, the levels of Cu, Mn, and Zn are higher than the reported WHO maximum permissible limits established for medicinal plants, just as previous studies have reported such high levels of essential metals in medicinal plants [71,72]. The population's health risk within the study was assessed based on the United States Environmental Protection Agency (USEPA) model, where a noncarcinogenic risk assessment of ingesting medicinal plants for children and adults in the study was established based on HQ and HI values.…”
Section: Discussioncontrasting
confidence: 45%
“…The ability to accumulate very high Zn amounts (up to 50 mg kg -1 ) was found for other species from the Thymus genus, e.g. T. serpyllum (Figas et al 2021 ). Ti concentration was within the toxicity thresholds for plants also in this species (Kabata-Pendias 2001 ).…”
Section: Resultsmentioning
confidence: 80%
“… Mineral and elemental composition in references: *Shahar et al ( 69 ) mg/100 g, **Abu-Darwish ( 70 ) ppm, ***Figas et al ( 71 ), ****Vasil'eva et al ( 72 ) mg/kg; Elements: K-potassium, Ca-calcium, Mg-magnesium, P-phosphorus, S-sulphur, Al-aluminium, Na-sodium, Cl-chlorine, Si-silicon, Fe-iron, Zn-zinc, Mn-manganese, Cu-copper, Ni-nickel, Co-cobalt, Cr-chromium, Pb-lead, Ba-barium, Sr-strontium. …”
Section: Resultsmentioning
confidence: 99%